1997
DOI: 10.1159/000291534
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation in Cord Blood at Birth: A Marker of Fetal Hypoxia during Labour

Abstract: Objective: This prospective study examined purine metabolism in relation to free oxygen radical activity, as reflected by lipid peroxide levels in umbilical cord blood at birth. Setting: Departments of Obstetrics and Gynaecology and of Chemical Pathology, the Chinese University of Hong Kong, Hong Kong, and Purine Research Laboratory, UMDS of Guy’s and St. Thomas’ Hospitals, London, UK. Methods: Umbilical cord arterial and venous blood samples were collected from 132 singleton term deliveries for determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 10 publications
(10 reference statements)
4
16
0
Order By: Relevance
“…Plasma MDA levels may vary from day to day within the subject and it can be acutely altered by smoking within hours [20]. Because of the rapid metabolism and wide variation of MDA, it is proposed that plasma organic hydroperoxides would be a better marker of free oxygen radical activity in the fetus [25].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma MDA levels may vary from day to day within the subject and it can be acutely altered by smoking within hours [20]. Because of the rapid metabolism and wide variation of MDA, it is proposed that plasma organic hydroperoxides would be a better marker of free oxygen radical activity in the fetus [25].…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between the cord blood and maternal blood lipid peroxide levels shows us that the fetus may be affected by the maternal oxidative stress. Intracellular hypoxia causes a decrease in the ATP levels and an increase in the ATP breakdown products [19,20]. A decrease in the ATP levels causes a destruction of the membrane sodium pump activity and oxidative phosphorylation fails.…”
Section: Discussionmentioning
confidence: 99%
“…This may trigger the lipid peroxidation. Rogers et al [20] showed that the increase in oxygen free radicals in the fetus is a sign of cellular hypoxia and reperfusion damage. On the other hand, Harkness et al [21] suggested that, in newborns with asphyxia, cord blood hypoxanthine levels were elevated and an elevated hypoxanthine catabolism by xanthine oxidase might be responsible for the increases in the free radical production.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have discounted the role of ischemia or hypoxia specifically at the time of birth in relation to the subsequent development of cerebral palsy, particularly in the preterm population, which is at highest risk for brain injury [2]. However, both direct brain injury as manifested by intraventricular hemorrhage (IVH) and periventricular leukomalacia (PVL), or later developmental abnormalities, have been correlated with some short-lived biochemical markers of ischemia or reperfusion, indicating that some proportion of neurological injury may relate to events near the time of birth [3][4][5]. One such marker is uric acid (UA) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%